The New Historical Novel and the Construction of Femininity in a Novel by Gioconda Belli - Camacho Guzmán, Gustavo (2018)
An analysis is presented on El pergamino de la seducción, by Gioconda Belli, about Juana de Castilla (1479-1555). The study refers to the construction of female characters (Juana de Castilla, Isabel La Católica, and Lucía). It is shown that although the novel attempts to revendicate female characters and the feminine figure as opposed to that of the male, there are underlying contradictions in their constructions regarding their position and the masculine figure.